THE PRACTICAL STATUS OF DEVELOPING STUDENTS' PROFESSIONAL-CREATIVE SKILLS IN AN INDIVIDUAL EDUCATIONAL ENVIRONMENT (Educator Insights: Journal of Teaching Theory and Practice, 2025)
Professional mastery of students is manifested in deep assimilation of acquired knowledge, solution of educational tasks, development of creative qualities. It is known that the process of personality development occurs under the influence of a number of factors. These are heredity, education and social environment. Motivation of learning, which is an element of education, plays an important role in preparing students for pedagogical activity. In addition to managing academic activity in the higher education system, it is also aimed at developing self-control and self-awareness in the student.